INFESTASI PLASMODIUM DALAM SUMSUM TULANG PENDERITA MALARIA - M. I. Diah P; Tonang D A; Lusi O W; J. B. Suparyatmo; Yuwono H S (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2007)
A 26-years-old man, was admitted to the hospital with the symptom of fever for 2 weeks. Differential diagnosis were pneumonia and lung tuberculosis, micrositic hypocromic anemia, and hyperglicemic stress. Bloodlood smear and bone marrow puncture showed infestation puncture showed infestation of Plasmodium falciparum and Plasmodium vivax. In this case, malaria infestation caused pancytopenia. Bone marrow aspiration in. In this case, malaria infestation caused pancytopenia. Bone marrow aspiration in malaria was useful for diagnostic and treatment monitoring.